Telework: job satisfaction during work from home among IT professionals in India: a cross sectional study - Shabadi, Nayanabai; Rao, Vadaga Vijaylakshmi; Murthy, M. R. Narayana; Ravali, Annaram (International Journal Of Community Medicine And Public Health, 2023)
Background: The untoward events of COVID-19 led to the enforcement of work from home (WFH) for nearly every wage earner across the globe. One of the several fields that saw its implications was the IT sector. We conducted the following study to understand how the IT techies have been affected by the shift in their workspace- from their cubicles at work to the tables at home and the implications of this shift on their general and mental health. Methods: A cross sectional study was conducted in January 2021. A Google form was circulated among IT professionals. Sample size was calculated by universal sampling technique. Data collected was entered in MS Excel and analysed using SPSS version 26. Results: Among the 47 received responses, the mean age group of the study sample was 20-30 years. 73.9% felt that personal obligations interrupted their work which led to increased frustration. There is also a rise in the incidences of backpain and eyestrain. The mean stress score of the study sample was 17.85±5.729 and though 80.9% felt they had a comfortable place at home to work, 62.52% of them wished to return to their workplace. Conclusions: Better innovative strategies need to be thought of and implemented to help employees have an efficient work-life balance.